Paradigmas y Polifuncionalidad : Estudio Diacrónico de «preciso»/«precisamente», «justo»/«justamente», «exacto»/«exactamente» Y «cabal»/«cabalmente». - Gerhalter, Katharina (Berlin/Boston : Walter de Gruyter GmbH, 2020)
The book series Beihefte zur Zeitschrift für romanische Philologie is among the most renowned publications in Romance Studies. It covers the entire field of Romance linguistics, including the national languages as well as the lesser studied Romance languages. The series publishes high-quality monographs and collected volumes on all areas of linguistic research, on medieval literature and on textual criticism.
Intro -- Agradecimientos -- Tabla de contenido -- Lista de gráficos -- Lista de tablas -- Introducción -- Primera Parte -- 1 Marco teórico y estado de la cuestión -- 2 Objetivos y metodología -- Segunda Parte -- 3 Análisis semasiológico -- 4 Análisis contrastivo -- Tercera Parte -- 5 Focalización -- 6 Afirmación -- 7 Reformulación -- 8 Conclusiones generales -- Bibliografía -- Índice de términos -- Abstract (in English).
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books